The Observed Experiences of Music Therapy on Parent-Child Interaction for Families with Children with Down Syndrome - O' Donoghue, Jess (Voices: A World Forum for Music Therapy, 2017)
The relationship between the quality of parent-child interactions and positive child development is well established in the literature. Nevertheless, parental and familial factors may pose risks to parents’ capacity to participate in quality interactions with their children. Families with a child with a disability in particular are more likely to experience social isolation, and higher levels of parenting stress. Early intervention programmes to promote positive parent-child interaction for these families is well recognised. However, there is a lack of literature about the effectiveness of such programmes for these families. This research study explores music therapy on parent-child interaction, specifically focusing on children with a diagnosis of Down syndrome (DS). This case study involves two in-depth cases of children diagnosed with DS and their primary caregivers. The study documents individual music therapy sessions which took place over a six week period. The case study materials were gathered through the researcher’s direct observations, fieldwork notes, and reflective journal logs. The music therapy block encouraged the primary caregivers to be more responsive during parent-child interactions. Furthermore, the children involved learned to engage and share musical activities with their mothers.